Advanced Preparation Techniques for Polymeric Nanoparticles and their Application in Drug Delivery - Bhardwaj, Harish; Sarthi, Soniya; Jangde, Rajendra Kumar (Pharmaceutical Nanotechnology, 2025)
Nanotechnology has advanced significantly in recent decades, with the production and design of nanomaterials becoming a focal point of research. Nanomedicine, a key component of this field, involves the development of nanoscale materials for applications in imaging and drug delivery. Current research predominantly focuses on the synthesis of precisely characterized nanomaterials, particularly in terms of their size and morphology, as these parameters play a critical role in determining the behavior of nanomaterials <span class=
Keywords: advantages